2019
DOI: 10.3389/fendo.2019.00153
|View full text |Cite
|
Sign up to set email alerts
|

Ginsenoside Rb2 Alleviates Obesity by Activation of Brown Fat and Induction of Browning of White Fat

Abstract: Ginsenoside Rb2 (Rb2), the most abundant saponin contained in Panax ginseng, has been used to treat variety of metabolic diseases. However, its effects in obesity and potential mechanisms are not well-understood. In the present study, we investigated metabolic performance with a Rb2 supplement in diet-induced obese (DIO) mice, focusing on the effects and mechanisms of Rb2 on brown and beige fat functions. Our results demonstrated that Rb2 effectively reduced body weight, improved insulin sensitivity, as well a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
37
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 49 publications
1
37
0
Order By: Relevance
“…As overfeeding processes escalate, hypertrophic adipocytes eventually overfill, yielding necrotic cellular debris and large lipid droplets to the detriment of neighbouring tissues, which play important roles in impairing insulin sensitivity. Indeed, the present report showed that Rb2 was effective in the control of weight gain and blood glucose levels in HFD-fed mice, which corroborated our previous study [ 17 , 18 ]. To further observe the effects of Rb2 on IR in vitro, we treated 3T3-L1 adipocytes with a TNF-α intervention to induce a classic IR cell model.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…As overfeeding processes escalate, hypertrophic adipocytes eventually overfill, yielding necrotic cellular debris and large lipid droplets to the detriment of neighbouring tissues, which play important roles in impairing insulin sensitivity. Indeed, the present report showed that Rb2 was effective in the control of weight gain and blood glucose levels in HFD-fed mice, which corroborated our previous study [ 17 , 18 ]. To further observe the effects of Rb2 on IR in vitro, we treated 3T3-L1 adipocytes with a TNF-α intervention to induce a classic IR cell model.…”
Section: Discussionsupporting
confidence: 93%
“…Rb2, which possesses various bioactivities including anti-inflammatory, anti-cancer and anti-obesity activities, has been studied for a long time [13,15,18,19]. However, there is little research exploring the mechanism by which Rb2 improves IR in obese mice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, it has been found that Rb1 induces browning through the regulation of PPARγ [22], PRDM16, PGC1α, and UCP1 [23] in 3T3-L1 adipocytes. In addition, Rb2 promotes browning of white fat in mice [24], and Rg1 induces browning by upregulating UCP1 expression and mitochondrial activity in white adipocyte [25]. Ginsenoside Rg3 is naturally present at a very low level or trace amounts in American ginseng root extract [26] and Asian ginseng [27].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a study found that ginsenoside Rb2 alleviated obesity by activation of brown fat and induction of browning of white fat, suggesting that Rb2 has effects on energy metabolism similar to Rd . Ginsenoside Rb2 and Rd are both PPD‐type ginsenosides.…”
Section: Discussionmentioning
confidence: 99%